RETRACTED: Efficient Diagnosis of Liver Disease using Support Vector Machine Optimized with Crows Search Algorithm - Devikanniga, D.; Ramu, Arulmurugan; Haldorai, Anandakumar (EAI Endorsed Transactions on Energy Web, 2020)
RETRACTED: The article has been retracted due to misconduct during the peer review process. The retraction notice can be found here: https://doi.org/10.4108/ew.13109
Keywords: Crow search algorithm; liver disease; sequential minimal optimization; support vector machine